Role of Socio-Demographic Factors, Stressful Life Events, College and Family Environment In Causation of Psychiatric Problems In Engineering Students - Pandey, Arun Kumar; Sapkota, Nidesh; Adhikari, Baikuntha Raj; Koirala, Parashar; Bhojak, Madan Mohan (Journal of Nobel Medical College, 2015)
Introduction: Professional college provides various opportunities for the all-round development of the students but they may also be subjected to various kinds of stressors. Engineering educational system is highly competitive and the students may face difficulties in both academic and personal life, sometime leading to psychiatric disorders. Material and Methods: This is a cross-sectional descriptive study from Malviya National Institute of Technology (MNIT), Jaipur the premier engineering college of Rajasthan and India. 196 students (1st year 50, 2nd year 51, 3rd year 48 and final year 47) were the subject for this study. In first phase, socio-demographic data sheet and GHQ-60 Hindi version to ascertain the extent of psychiatric illnesses was administered. False positive cases were dropped and then diagnosed students with psychiatric problems and control group were administered tests to find out the role of probable contributing factors. Results were analyzed and suitable statistical procedure was applied. Result and Conclusion: Forty eight out of one hundred ninety six students i.e. 24.49% had some psychiatric disorders. Engineering students from lower income group, Hindi as their medium of study before entering Engineering College than students with English background, students from nuclear family than from joint family and students from urban background has higher rate of psychiatric illness in all the groups. Family and college environment was also a contributing factor. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12238 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Pqge: 52-60